Moisture-permeable film and application thereof

By distributing functionalized one-dimensional nanomaterials and gold nanomaterials in the moisture-permeable film, using near-infrared light irradiation to improve the transfer rate and efficiency of water molecules, the condensate discharge problem is solved, and the airtightness and mechanical strength of the film are enhanced, achieving better use effect and life.

CN119752077APending Publication Date: 2025-04-04SHENZHEN SENIOR TECH MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979333.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During use, the existing moisture-permeable film cannot be discharged quickly due to the condensation water, which affects the use effect and life, and is insufficient in airtightness and mechanical strength.

Method used

Functional one-dimensional nanomaterials and gold nanomaterials are used to generate photothermal conversion by near-infrared light irradiation, resulting in the shrinkage of the temperature-sensitive polymer chain, forming microscopic channels to improve the rate and efficiency of water molecules, and the airtightness and mechanical strength of the film are improved through the entanglement of the one-dimensional nanomaterial.

Benefits of technology

It realizes the rapid discharge of condensate water on the surface of the moisture-permeable film, improves the rate and efficiency of water molecules, enhances the airtightness and mechanical strength of the film, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221182750000161
    Figure BDA0005221182750000161
Patent Text Reader

Abstract

The invention provides a moisture permeable film and application thereof. The moisture-permeable film comprises a base film, and a functionalized one-dimensional nano material and a gold nano material which are distributed in the base film, the functionalized one-dimensional nano-material comprises a one-dimensional nano-material of which the surface is grafted with a thermo-sensitive polymer; the gold nanomaterial is in coordination connection with the temperature-sensitive polymer. According to the moisture-permeable film disclosed by the invention, the problems that the use effect of the moisture-permeable film is influenced due to the fact that condensed water cannot be quickly discharged in the prior art and the air tightness and the mechanical strength of the existing moisture-permeable film are poor are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane materials, and in particular relates to a moisture permeable membrane and application thereof. Background Art

[0002] A breathable membrane is a special membrane material that can be used as a cling film, a full heat exchange membrane, etc. Its breathable effect is related to the transfer rate and efficiency of water molecules. However, during use, condensed water often forms on the surface of the membrane due to oversaturation of air humidity or temperature changes. If the condensed water cannot be quickly discharged, it will affect the use effect and life of the breathable membrane; and the air tightness and mechanical strength of existing breathable membranes need to be further improved; therefore, the development of a breathable membrane that can intelligently remove condensed water on the surface, has a fast water molecule transfer rate, high efficiency, good air tightness and high mechanical strength, is a problem that needs to be solved in this field. Summary of the invention

[0003] In view of the shortcomings of the prior art, the present invention aims to provide a breathable membrane and a preparation method and application thereof. The breathable membrane solves the problems in the prior art that condensed water cannot be quickly discharged, affecting the use effect of the breathable membrane, and the existing breathable membrane has poor air tightness and low mechanical strength.

[0004] To achieve this object, the present invention adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a moisture permeable membrane, which includes a base membrane and functionalized one-dimensional nanomaterials and gold nanomaterials distributed in the base membrane; the functionalized one-dimensional nanomaterials include one-dimensional nanomaterials with thermosensitive polymers grafted on the surface; the gold nanomaterials are coordinated and connected to the thermosensitive polymers.

[0006] In the present invention, the moisture permeable film continuously absorbs and transfers water molecules during use, the thermosensitive polymer and the water molecules interact and combine, the polymer chain is fully extended, and there is basically no gap between the functionalized one-dimensional nanomaterial and the base film body. When receiving near-infrared light irradiation, the gold nanomaterial can produce a photothermal conversion phenomenon due to the plasma resonance effect, generating a large amount of heat; the generated heat makes the temperature-responsive thermosensitive polymer chain segment no longer stretch freely, but shrinks and collapses to the surface of the one-dimensional nanomaterial, thereby forming and enlarging microscopic channels between the functionalized one-dimensional nanomaterial and the base film, and the water molecule transfer rate and transfer efficiency are significantly improved; and the one-dimensional nanomaterial is a linear material, which is dispersed in the entire base film, and when the thermosensitive polymer shrinks, it helps to further increase the microscopic channels, improve the water molecule transfer rate and transfer efficiency; avoid affecting the use effect of the moisture permeable film due to the inability to quickly discharge condensed water; when the condensed water is removed, the near-infrared light irradiation is ended, the thermosensitive polymer on the surface of the functionalized one-dimensional nanomaterial restores its original morphological characteristics, the microchannel shrinks, and the water molecule transfer rate restores to the level before irradiation, ensuring the good performance of the membrane. In addition, the one-dimensional nanomaterial has a strong entanglement with the base film, and forms a dense film layer in the form of polymer chain entanglement, which is beneficial to improving the density of the moisture permeable film, so that the moisture permeable film has good air tightness and mechanical strength.

[0007] In a second aspect, the present invention provides a use of the moisture-permeable film as described in the first aspect in a cling film or a total heat exchange membrane.

[0008] In the present invention, the moisture permeable film is used as a fresh-keeping film to extend the shelf life of food and prevent food from rotting due to the failure to discharge condensed water in time; it is used as a full heat exchange membrane to improve the enthalpy efficiency of heat exchange; and the moisture permeable membrane has good mechanical properties. During use, the moisture permeable membrane is resistant to stretching and has little deformation, and can maintain the structural integrity of the membrane, thereby extending the service life of the membrane.

[0009] Compared with the prior art, the present invention has the following beneficial effects:

[0010] The moisture permeable membrane provided by the present invention, by adding specific functionalized one-dimensional nanomaterials and gold nanomaterials, is conducive to improving the water molecule transfer rate and efficiency of the membrane under near-infrared light irradiation, so that condensed water on the surface of the membrane can be discharged promptly and quickly, avoiding the influence of condensed water on the use effect of the moisture permeable membrane, and the obtained moisture permeable membrane has good density, good air tightness and mechanical strength. DETAILED DESCRIPTION

[0011] The technical scheme of the present invention is further described below by specific embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In the embodiments of the present invention, if specific conditions are not specified, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0012] The invention provides a moisture permeable film, which comprises a base film and a functionalized one-dimensional nanomaterial and a gold nanomaterial distributed in the base film; the functionalized one-dimensional nanomaterial comprises a one-dimensional nanomaterial with a thermosensitive polymer grafted on the surface; and the gold nanomaterial is coordinated and connected with the thermosensitive polymer.

[0013] In the present invention, the moisture permeable membrane has specific functionalized one-dimensional nanomaterials distributed in the base membrane, which is beneficial to improving the water molecule transfer rate and efficiency of the membrane under near-infrared light irradiation, so that condensed water on the surface of the membrane can be discharged promptly and quickly, avoiding the influence of condensed water on the use effect of the moisture permeable membrane, and the obtained moisture permeable membrane has good density, good air tightness and mechanical strength.

[0014] It should be noted that the coordination connection in the present invention means that the gold nanomaterial and the thermosensitive polymer can be connected to each other through a coordinated covalent bond formed by sharing lone pair electrons or an ionic bond formed by electrostatic attraction.

[0015] It should be noted that the base film in the present invention is a non-porous dense film.

[0016] Preferably, the raw material of the one-dimensional nanomaterial comprises one or a combination of at least two of an inorganic compound or an organic compound.

[0017] The raw material of the one-dimensional nanomaterial does not contain metal single material, such as gold, silver, iron, copper, chromium, etc. The raw material of the one-dimensional nanomaterial is selected from one or a combination of at least two of inorganic compounds or organic compounds, which is conducive to the grafting and good bonding of the thermosensitive polymer.

[0018] Preferably, the inorganic compound includes at least one of aluminum oxide, zinc oxide, magnesium oxide, calcium carbonate, calcium sulfate, silicon carbide, potassium titanate, aluminum borate, silicon nitride, aluminum nitride, boron nitride, and hydroxyapatite.

[0019] Preferably, the organic compound includes at least one of cellulose and chitin.

[0020] Preferably, the one-dimensional nanomaterial may be at least one of nanofiber and nanocrystal according to its morphological characteristics.

[0021] Preferably, the nanofiber may be a nanofiber having a diameter less than 1 μm and a fibril-like shape with an aspect ratio of 5 or more.

[0022] Preferably, the length of the one-dimensional nanomaterial is 200nm to 2000nm, for example, it can be 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm or a range consisting of any two of them; the diameter is 20nm to 100nm, for example, it can be 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm or a range consisting of any two of them.

[0023] Preferably, the aspect ratio of the one-dimensional nanomaterial is 10 to 100, for example, it can be 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 80, 82, 84, 86, 88, 90, 92, 94, 96, 98, 100 or a range consisting of any two of them.

[0024] In the present invention, the length, diameter and aspect ratio of the one-dimensional nanomaterial are within the above ranges, which is conducive to a more uniform dispersion of the functionalized one-dimensional nanomaterial in the base film, thereby further facilitating the good structural density of the moisture permeable film, thereby improving its mechanical strength and air tightness while further improving the moisture permeability effect.

[0025] In the present invention, the length and diameter of the one-dimensional nano material can be observed by a scanning electron microscope (SEM) or a transmission electron microscope (TEM). For example, a transmission electron microscope (TEM) (Hitachi High-Technologies, model H-7650) can be used to take 10 photos at 100,000 to 200,000 times, and the diameter and length of 50 one-dimensional nano materials can be measured on the shooting screen by the software attached to the TEM, and the length and diameter of the one-dimensional nano material can be obtained as the arithmetic mean.

[0026] Preferably, the mass of the functionalized one-dimensional nanomaterial is 6% to 30% of the mass of the base film, for example, it can be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or a range consisting of any two of them.

[0027] The mass of the functionalized one-dimensional nanomaterial is 6% to 30% of the mass of the base film, which is beneficial to further improve the mechanical strength of the moisture permeable film while further ensuring good air tightness and forming better and more suitable micro channels.

[0028] Preferably, the thermosensitive polymer contains an amino group in its molecular structure.

[0029] Preferably, the temperature-sensitive polymer includes a polymer formed from at least one of N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, and derivatives thereof.

[0030] In the present invention, the molecular structure of the thermosensitive polymer contains an amino group, which can coordinate with the gold nanomaterial to form an electron donor-electron acceptor of Au-N, thereby stably loading the gold nanomaterial on the thermosensitive polymer; the amino group can be a primary amine, a secondary amine, a tertiary amine, etc.

[0031] In the present invention, the derivative refers to a compound that can be obtained by introducing a new functional group into the molecular structure of the thermosensitive polymer monomer or changing its structure through chemical modification according to actual use requirements. For example, the derivative of PDMAEMA can be PDMAEMA-N3, β-cyclodextrin-poly methacrylate N, N-dimethylaminoethyl ester (β-CD-PDMAEMA), a block copolymer of poly methacrylate N, N-dimethylaminoethyl ester (PDMAEMA) and polycaprolactone (PCL) (PCL-b-PDMAEMA), polylactic acid (PLA) and PDMAEMA-N3, and a block copolymer of polylactic acid (PLA) and PDMAEMA-N3. A forms a block copolymer (PLA-b-PDMAEMA), hydroxyethyl cellulose (HEC) is modified and grafted with poly [methacrylic acid (N,N-diethylaminoethyl)] (PDEAEMA) to form a HEC-PDMAEMA grafted modified polymer, etc.; the derivatives of PDEAEMA can be polyethylene glycol (PEG) modified PDEAEMA, polylactic acid (PLA) and PDEAEMA form a block copolymer (PLA-b-PDEAEMA), hydroxyethyl cellulose (HEC) is modified and grafted with PDEAEMA to form a HEC-PDEAEMA grafted polymer, etc.

[0032] Preferably, the grafting content of the thermosensitive polymer in the one-dimensional nanomaterial is 2wt% to 20wt%, for example, it can be 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% or a range consisting of any two of them.

[0033] The grafting content of the temperature-sensitive polymer in the one-dimensional nanomaterial is 2wt% to 20wt%, which is beneficial to further improve the moisture permeability, mechanical strength and air tightness of the moisture permeable film.

[0034] Preferably, the weight average molecular weight of the thermosensitive polymer is 2KDa to 20KDa (i.e., 2000Da to 20000Da), for example, it can be 2KDa, 3KDa, 4KDa, 5KDa, 6KDa, 7KDa, 8KDa, 9KDa, 10KDa, 11KDa, 12KDa, 13KDa, 14KDa, 15KDa, 16KDa, 17KDa, 18KDa, 19KDa, 20KDa or a range consisting of any two of them.

[0035] In the present invention, the weight average molecular weight of the thermosensitive polymer can be tested by gel permeation chromatography (GPC); the weight average molecular weight of the thermosensitive polymer is in the range of 2KDa to 20KDa, which is conducive to forming good microscopic channels, thereby further improving moisture permeability and air tightness.

[0036] Preferably, based on the total mass of the functionalized one-dimensional nanomaterial as 100%, the mass of the gold nanomaterial is 0.5% to 2%, for example, it can be 0.5%, 0.52%, 0.54%, 0.56%, 0.58%, 0.6%, 0.62%, 0.65%, 0.68%, 0.7%, 0.72%, 0.75%, 0.78%, 0.8%, 0.82%, 0.85%, 0.88%, 0.9%, 0.92%, 0.95%, 0.98%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or the range of any two thereof.

[0037] In the present invention, the mass of the gold nanomaterial is in the range of 0.5% to 2%, which is beneficial to further improve the change rate of water molecule transfer rate.

[0038] Preferably, the gold nanomaterial comprises at least one of the following:

[0039] a), gold nanoparticles with an average particle size of 50nm to 150nm; for example, it can be 50nm, 52nm, 55nm, 58nm, 60nm, 62nm, 65nm, 68nm, 70nm, 72nm, 75nm, 78nm, 80nm, 82nm, 85nm, 88nm, 90nm, 92nm, 95nm, 98nm, 100nm, 102nm, 105nm, 108nm, 110nm, 112nm, 115nm, 118nm, 120nm, 122nm, 125nm, 128nm, 130nm, 132nm, 135nm, 138nm, 140nm, 142nm, 145nm, 148nm, 150nm or a range consisting of any two of them.

[0040] b) One-dimensional gold nanomaterials with an aspect ratio of 5 to 20; for example, 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, 7, 7.2, 7.5, 7.8, 8, 8.2, 8.5, 8.8, 9, 9.2, 9.5, 9.8, 10, 10.2, 10.5, 10.8, 11, 11.2, 11.5, 11.8, 12, 12.2, 12.5, 1 19.2, 19.5, 19.8, 20, or a range consisting of any two of these.

[0041] c), a length of 20nm to 125nm (for example, 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 48nm, 50nm, 52nm, 54nm, 56nm, 58nm, 60nm, 62nm, 64nm, 66nm, 68nm, 70nm, 72nm, 74nm, 76nm, 78nm, 80nm, 82nm, 84nm, 86nm, 88nm, 90nm, 92nm, 94nm, 96nm, 98nm m, 100nm, 102nm, 105nm, 108nm, 110nm, 112nm, 115nm, 118nm, 120nm, 122nm, 125nm or a range consisting of any two thereof), and a one-dimensional gold nanomaterial with a diameter of 5nm to 25nm (for example, it can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm or a range consisting of any two thereof).

[0042] Preferably, the thickness of the moisture permeable membrane is 0.6 μm to 3 μm, for example, it can be 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm or a range consisting of any two of them.

[0043] In the present invention, the thickness of the moisture permeable membrane is in the range of 0.6 μm to 3 μm, which is beneficial for the moisture permeable membrane to have suitable mechanical strength and suitable water molecule transmission path.

[0044] The present invention also provides a method for preparing the moisture-permeable membrane according to the first aspect, the method comprising the following steps:

[0045] S1, mixing the functionalized one-dimensional nanomaterial with the gold nanomaterial, and drying to form a mixed system;

[0046] S2. Mixing the raw materials of the base film with the mixed system to form a film to obtain the moisture-permeable film.

[0047] Preferably, the raw material of the base membrane includes a polymer, and the weight average molecular weight of the polymer is 40KDa to 100KDa (i.e., 40000Da to 100000Da), for example, it can be 40KDa, 45KDa, 50KDa, 55KDa, 60KDa, 65KDa, 70KDa, 75KDa, 80KDa, 85KDa, 90KDa, 95KDa, 100KDa or a range consisting of any two of them; the weight average molecular weight of the polymer can be measured by GPC.

[0048] In the present invention, the weight average molecular weight of the polymer is selected within the range of 40KDa to 100KDa, which is beneficial to the compactness of the film.

[0049] Preferably, the polymer includes at least one of polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO), polymethacrylic acid (PMAA), polyacrylic acid (PAA), hydroxypropyl methylcellulose (HPMC) or hyaluronic acid (HA).

[0050] It should be noted that the raw materials of the above-mentioned base film can be mixed with additives such as phenol-based, phosphorus-based or sulfur-based antioxidants, metal soaps such as calcium stearate or zinc stearate, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, coloring pigments, etc. as needed.

[0051] In the present invention, the preparation method of the functionalized one-dimensional nanomaterial in step S1 may be any existing preparation method capable of grafting a thermosensitive polymer on the surface of a one-dimensional nanomaterial.

[0052] For example, a pre-polymerized thermosensitive polymer can be chemically grafted onto the active site of a one-dimensional nanomaterial to form a functionalized one-dimensional nanomaterial with a surface-grafted thermosensitive polymer; or the active center of an activated one-dimensional nanomaterial can be used to initiate the polymerization of the monomers of the thermosensitive polymer to generate a grafted polymer to form a functionalized one-dimensional nanomaterial with a surface-grafted thermosensitive polymer.

[0053] Specifically, the method for preparing the functionalized one-dimensional nanomaterial may include the following steps:

[0054] A one-dimensional nanomaterial macromolecular initiation system is obtained by grafting an initiator or a chain transfer agent on the surface of a one-dimensional nanomaterial containing at least one of a hydroxyl group and an amino group; and then the one-dimensional nanomaterial macromolecular initiation system is reacted with a monomer of a thermosensitive polymer to obtain the one-dimensional nanomaterial grafted with the thermosensitive polymer;

[0055] The initiator may be, for example, 2-bromoisobutyryl bromide, 2-bromoisobutyryl chloride, 2-chloroisobutyryl chloride, etc.; the chain transfer agent may be, for example, 2-cyano-2-propylbenzodisulfide (CPDB), 2-(dodecyltrithiocarbonate)-2-methylpropionic acid (DDMAT), 4-cyano-4-(phenylcarbonylthio)pentanoic acid, 4-cyano-4-[(dodecylsulfanylsulfanylcarbonyl)sulfanyl]pentanoic acid, etc.

[0056] The one-dimensional nanomaterial may contain at least one of hydroxyl and amino groups, or at least one of hydroxyl and amino groups may be introduced onto the surface of the one-dimensional nanomaterial through modification. Specifically, the modification may use, for example, a silane coupling agent.

[0057] Other additives, such as catalysts, etc., may also be added to the reaction system.

[0058] The catalyst can be copper bromide, cuprous bromide, or the like.

[0059] The step S1 of mixing the functionalized one-dimensional nanomaterial with the gold nanomaterial may specifically be mixing the obtained functionalized one-dimensional nanomaterial grafted with the thermosensitive polymer with the gold nanomaterial and the first solvent, and drying to form a mixed system.

[0060] The first solvent may be water, dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), or the like.

[0061] In the present invention, the functionalized one-dimensional nanomaterial, the gold nanomaterial and the first solvent are mixed at a temperature of 20° C. to 30° C. and for a time of 4 h to 24 h.

[0062] In the present invention, when the first solvent is an organic solvent, the mixed system may further include a dialysis step before drying.

[0063] In the present invention, the step S2 may specifically be to mix the raw material of the base film with the mixed system and the second solvent, and the mixing temperature may be 20°C to 30°C.

[0064] The second solvent may be water, dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), or the like.

[0065] In the present invention, the film forming method is not particularly limited, and the film can be prepared using an existing film forming method.

[0066] Preferably, the film forming method may be a coating method or a casting method.

[0067] In the present invention, the coating method or the casting method is performed on the surface of a substrate and solidified, and the substrate includes a polyethylene terephthalate (PET) release film or glass.

[0068] Preferably, the film forming process further includes a peeling step.

[0069] The present invention also provides a use of the moisture-permeable film as described in the first aspect in a fresh-keeping film or a total heat exchange membrane.

[0070] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0071] The technical solution provided by the present invention will be clearly and completely described below in conjunction with examples and comparative examples. Obviously, the specific implementation methods described are only part of the implementation methods of the present invention, rather than all the implementation methods.

[0072] The materials used in the present invention can be purchased from the market or prepared by conventional methods; unless otherwise specified, the materials used in the present invention are as follows:

[0073] Materials of base film:

[0074] PVA: weight average molecular weight is 75 KDa, purchased from Anhui Wanwei.

[0075] PMAA: weight average molecular weight is 120 KDa, purchased from Aladdin Reagents.

[0076] PEO: weight average molecular weight is 100 KDa, purchased from Aladdin Reagents.

[0077] Gold nanomaterials: purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.

[0078] Cellulose nanofibers were purchased from Henan Kegao.

[0079] Example 1

[0080] The present embodiment provides a moisture permeable membrane, which has a thickness of 1.5 μm and comprises a PVA base membrane and functionalized cellulose nanofibers and gold nanoparticles distributed in the PVA base membrane; the functionalized cellulose nanofibers are cellulose nanofibers with poly (N,N-dimethylaminoethyl methacrylate) (PDMAEMA) grafted on the surface; the gold nanoparticles are coordinated and connected with PDMAEMA; the cellulose nanofibers have a length of 300 nm, a diameter of 20 nm, and an aspect ratio of 15; the average particle size of the gold nanoparticles is 80 nm; the grafting content of PDMAEMA is 4 wt %; the weight average molecular weight of PDMAEMA is 3 KDa; the mass of the gold nanoparticles is 0.5 % of the total mass of the cellulose nanofibers grafted with PDMAEMA; and the mass of the functionalized cellulose nanofibers is 8 % of the mass of the base membrane.

[0081] This embodiment provides a method for preparing the moisture permeable membrane, which specifically comprises the following steps:

[0082] S1: Disperse cellulose nanofibers in dichloromethane to obtain a cellulose nanofiber dispersion with a mass concentration of 5%; add 5% solvent mass of acid-binding agent triethylamine thereto, slowly add 2% mass of 2-bromoisobutyryl bromide (based on the mass of cellulose nanofibers as 100%) at a temperature of 0°C and under stirring, react for 3 hours, repeatedly wash with water for 3 times, and dry to obtain a cellulose nanofiber macroinitiator; mix 1.5g of the cellulose nanofiber macroinitiator with 49g of toluene to obtain a mixed solution with a mass concentration of 3%, and then add 0.05g of catalyst cuprous bromide, 0.1g of multidentate nitrogen ligand 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA) and a formulated amount of DMAEMA in sequence, react at 90°C for 5 hours under argon protection to obtain cellulose nanofibers grafted with thermosensitive PDMAEMA.

[0083] S2: According to the formula, the cellulose nanofibers grafted with thermosensitive PDMAEMA obtained in S1 and gold nanoparticles were dispersed in dimethyl sulfoxide (DMSO) at 26° C. for 10 minutes, then dialyzed with deionized water for 24 hours, and freeze-dried to obtain the functionalized cellulose nanofibers.

[0084] S3: At 26°C, PVA and the functionalized cellulose nanofibers obtained in S2 (the mass of the functionalized cellulose nanofibers is 8% of that of PVA) are dispersed in deionized water to obtain a mixed solution; the mixed solution is applied to the glass surface, dried and solidified at 60°C, and peeled off to obtain the moisture permeable membrane.

[0085] Example 2

[0086] The present embodiment provides a moisture permeable membrane, which has a thickness of 1 μm and includes a PEO base membrane and functionalized cellulose nanofibers and one-dimensional gold nanomaterials distributed in the PEO base membrane; the functionalized nanofibers are cellulose nanofibers with polymethacrylate (N,N-diethylaminoethyl ester) (PDEAEMA) grafted on the surface; the one-dimensional gold nanomaterial is coordinated and connected with PDEAEMA; the cellulose nanofibers have a length of 800 nm, a diameter of 32 nm, and an aspect ratio of 25; the one-dimensional gold nanomaterial has a length of 100 nm, a diameter of 20 nm (aspect ratio of 5); the grafting content of PDEAEMA is 10wt%; the weight average molecular weight of PDEAEMA is 12KDa; the mass of the one-dimensional gold nanomaterial is 1% of the total mass of the cellulose nanofibers grafted with PDEAEMA; the mass of the functionalized cellulose nanofibers is 15% of the mass of the base membrane.

[0087] This embodiment provides a method for preparing the moisture permeable membrane, which is different from the embodiment 1 only in that corresponding adjustments are made according to the formula; other steps and parameters are the same as those in the embodiment 1.

[0088] Example 3

[0089] The present embodiment provides a moisture permeable membrane, which has a thickness of 2.5 μm and comprises a PMAA base membrane and functionalized cellulose nanofibers and gold nanoparticles distributed in the PMAA base membrane; the functionalized cellulose nanofibers are cellulose nanofibers with PDMAEMA grafted on the surface; the gold nanoparticles are coordinated and connected with PDMAEMA; the cellulose nanofibers have a length of 2000 nm, a diameter of 50 nm, and an aspect ratio of 40; the average particle size of the gold nanoparticles is 150 nm; the grafting content of PDMAEMA is 18 wt %; the weight average molecular weight of PDMAEMA is 19 KDa; the mass of the gold nanoparticles is 2% of the total mass of the cellulose nanofibers grafted with PDMAEMA; and the mass of the functionalized cellulose nanofibers is 28% of the mass of the base membrane.

[0090] This embodiment provides a method for preparing the moisture permeable membrane, which is different from the embodiment 1 only in that corresponding adjustments are made according to the formula; other steps and parameters are the same as those in the embodiment 1.

[0091] Example 4

[0092] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the length of the cellulose nanofiber is 400 nm, the diameter is 50 nm, and the aspect ratio is 8. Other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0093] Example 5

[0094] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the length of the cellulose nanofiber is 2400 nm, the diameter is 20 nm, and the aspect ratio is 120. Other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0095] Example 6

[0096] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the length of the cellulose nanofiber is 100 nm, the diameter is 5 nm, and the aspect ratio is 20. Other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0097] Example 7

[0098] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the length of the cellulose nanofiber is 2500 nm, the diameter is 125 nm, and the aspect ratio is 20. Other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0099] Example 8

[0100] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the grafted content of PDMAEMA is 1 wt %. Other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0101] Example 9

[0102] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the grafted content of PDMAEMA is 24 wt %, and other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0103] Example 10

[0104] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the weight average molecular weight of the PDMAEMA is 1 KDa, and other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0105] Embodiment 11

[0106] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the weight average molecular weight of the PDMAEMA is 25 KDa, and other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0107] Example 12

[0108] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the mass of the gold nanoparticles is 0.2% of the total mass of the cellulose nanofibers grafted with PDMAEMA, and other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0109] Example 13

[0110] This embodiment provides a moisture permeable membrane, which is different from the embodiment 1 only in that the mass of the gold nanoparticles is 4% of the total mass of the cellulose nanofibers grafted with PDMAEMA, and other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0111] Embodiment 14

[0112] This embodiment provides a moisture permeable film, which is different from the embodiment 1 only in that the mass of the functionalized cellulose nanofibers is 4% of the mass of the base film, and other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0113] Embodiment 15

[0114] This embodiment provides a moisture permeable film, which is different from the embodiment 1 only in that the mass of the functionalized cellulose nanofibers is 35% of the mass of the base film, and other materials, amounts and preparation methods are the same as those in the embodiment 1.

[0115] Comparative Example 1

[0116] This comparative example provides a moisture permeable membrane, which is different from Example 1 only in that there are no cellulose nanofibers in the moisture permeable membrane, and in step S1 of the preparation method, the cellulose nanofiber macromolecular initiator is replaced by an equimolar amount of 2-bromoisobutyryl bromide, and other materials, amounts and preparation methods are the same as those in Example 1.

[0117] Comparative Example 2

[0118] This comparative example provides a moisture permeable membrane, which is different from Example 1 only in that the moisture permeable membrane does not contain gold nanoparticles, and in the preparation method, step S2 is not performed, and other materials, amounts and preparation methods are the same as those in Example 1.

[0119] Comparative Example 3

[0120] This comparative example provides a moisture permeable membrane, which is different from Example 1 only in that the moisture permeable membrane does not contain functionalized cellulose nanofibers and gold nanoparticles, and other materials, amounts and preparation methods are the same as those in Example 1.

[0121] Performance Testing

[0122] The following performance tests were performed on the moisture permeable membranes provided in Examples 1 to 15 and Comparative Examples 1 to 3.

[0123] (1) Water molecule transmission rate: Referring to the standard GB / T 1037-2021, the water molecule transmission rate of the moisture permeable film before and after 30 minutes of near-infrared light (wavelength 780nm-1100nm) irradiation was tested at 38°C and 90% relative humidity; and the change rate of the water molecule transmission rate was calculated; wherein, the change rate of the water molecule transmission rate = (water molecule transmission rate after 30 minutes of irradiation - water molecule transmission rate before irradiation) / water molecule transmission rate before irradiation × 100%.

[0124] (2) Air permeability: Referring to the standard GB / T 36363-2018, the air permeability of the moisture permeable film before and after near-infrared light irradiation was tested; and the air permeability change rate was calculated; wherein, the air permeability change rate = (air permeability after irradiation for 30 minutes - air permeability before irradiation) / air permeability before irradiation × 100%.

[0125] (3) Tensile strength: Tested in accordance with GB / T 36363-2018.

[0126] The specific test results are shown in Table 1.

[0127] Table 1

[0128]

[0129] As can be seen from Table 1, the breathable membrane provided by the present invention is distributed with specific functionalized one-dimensional nanomaterials and gold nanomaterials in the base membrane, which is beneficial to improve the water molecule transfer rate and efficiency of the breathable membrane under near-infrared light irradiation, so that the condensed water on the surface of the membrane can be discharged promptly and quickly, avoiding the influence of condensed water on the use effect of the breathable membrane, and the obtained breathable membrane has good density, good air tightness and mechanical strength; it can be seen from Example 1 and Comparative Example 1 that there is no one-dimensional nanomaterial in the breathable membrane, and the moisture permeability and the moisture permeability change rate after infrared irradiation are poor, and the air tightness is also reduced, and the mechanical strength is equivalent to the base membrane and is not significantly improved; it can be seen from Comparative Examples 2 and 3 that at least one of the functionalized one-dimensional nanomaterials and the gold nanomaterials is not added to the breathable membrane, and the breathable membrane does not have the effect of accelerating the water molecule transfer rate before and after near-infrared light irradiation, and it is impossible to accelerate the transfer rate of water molecules under near-infrared light irradiation to obtain better moisture permeability.

[0130] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A moisture permeable film, characterized in that The moisture permeable film comprises a base film and functionalized one-dimensional nanomaterials and gold nanomaterials distributed in the base film; The functionalized one-dimensional nanomaterial includes a one-dimensional nanomaterial with a thermosensitive polymer grafted on the surface; The gold nanomaterial is coordinated and connected with the thermosensitive polymer.

2. The moisture-permeable film according to claim 1, characterized in that The raw material of the one-dimensional nanomaterial comprises one or a combination of at least two of an inorganic compound or an organic compound; Preferably, the inorganic compound includes at least one of aluminum oxide, zinc oxide, magnesium oxide, calcium carbonate, calcium sulfate, silicon carbide, potassium titanate, aluminum borate, silicon nitride, aluminum nitride, boron nitride, and hydroxyapatite; Preferably, the organic compound includes at least one of cellulose and chitin.

3. The moisture-permeable film according to claim 1 or 2, characterized in that The one-dimensional nanomaterial has a length of 200nm to 2000nm and a diameter of 20nm to 100nm; Preferably, the one-dimensional nanomaterial has an aspect ratio of 10-100.

4. The moisture-permeable film according to any one of claims 1 to 3, characterized in that The mass of the functionalized one-dimensional nano material is 6% to 30% of the mass of the base film.

5. The moisture-permeable film according to any one of claims 1 to 4, characterized in that The molecular structure of the thermosensitive polymer contains an amino group; Preferably, the temperature-sensitive polymer includes a polymer formed from at least one of N,N-dimethylaminoethyl methacrylate, (N,N-diethylaminoethyl methacrylate), and derivatives thereof.

6. The moisture-permeable film according to any one of claims 1 to 5, characterized in that The grafting content of the temperature-sensitive polymer in the one-dimensional nanomaterial is 2 wt% to 20 wt%.

7. The moisture-permeable film according to any one of claims 1 to 6, characterized in that The weight average molecular weight of the thermosensitive polymer is 2KDa to 20KDa.

8. The moisture-permeable film according to any one of claims 1 to 7, characterized in that Taking the total mass of the functionalized one-dimensional nanomaterial as 100%, the mass of the gold nanomaterial is 0.5% to 2%.

9. The moisture-permeable film according to any one of claims 1 to 8, characterized in that The gold nanomaterial comprises at least one of the following: a) Gold nanoparticles with an average particle size of 50nm to 150nm; b) One-dimensional gold nanomaterials with an aspect ratio of 5 to 20; c) One-dimensional gold nanomaterials with a length of 20nm to 125nm and a diameter of 5nm to 25nm.

10. Use of the moisture permeable film according to any one of claims 1 to 9 in a cling film or a total heat exchange membrane.